Perancangan Produksi Video Dokumenter Merangkai Keindahan Menganyam Harapan Sebagai Media Promosi Kerajinan Rangkaian Bunga Nusantara - Kamilah, Eka Putri; Almanzhani, Shifa Amalia; Hanafi, Ardiansyah Rizal; Kurnia, Kurnia (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
Weaving Beauty, Weaving Hope is the idea of a short documentary video work which is designed as a work object analyzed in depth to be able to communicate the meaning behind the creation of the flower arrangement. Based on these phenomena and problems, the aim of designing the documentary short video work Arranging the Beauty of Weaving Hope is to understand how to design a short documentary video production to promote the value of the product so that it can persuade consumer decisions. The project for making this work is a documentary video entitled "Creating the Beauty of Weaving Hope". This work tells the story behind the creation of the Indonesian Flower Basket Series from Bouquet Bucket, which is a form of appreciation and harmony towards local Indonesian woven bamboo crafts. In making this promotional documentary video, the creator of the work is to inform and educate the public about making products related to Indonesian craftsmen. Based on the results of the YouTube social media promotional documentary video entitled "Creating the Beauty of Weaving Hope" it has fulfilled the author's hopes. The hope of the author of this YouTube social media promotional documentary video is that it can fulfill the requirements for obtaining a Bachelor's degree in Communication Science, provide information about product making and provide education related to Indonesian cultural crafts. The aim of this work is to build understanding of Bouquet Bucket consumers so that they are aware of the importance of choosing the work of local craftsmen to appreciate the preservation of Indonesian culture.